Good Environmental Governance in the Protection and Sustainable Management of Peatlands in Bukit Batu District, Bengkalis Regency - M. Arphin Dita (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the implementation of Good Environmental Governance (GEG) in the protection and sustainable management of peatlands in Bukit Batu District, Bengkalis Regency. The vast peatlands in this area face various environmental issues, including recurring forest fires, ecosystem degradation, and the threat of climate change. Using a qualitative and phenomenological approach, this research explores the principles of GEG such as transparency, community participation, accountability, and efficiency in peatland management. The findings indicate that despite various efforts by the local government and community in managing peatlands, the main challenges lie in weak supervision, low environmental awareness, and the suboptimal implementation of policies. Therefore, strengthening institutional capacity and active community participation are key to achieving sustainable peatland management. It is hoped that the results of this study can provide strategic recommendations for more effective and inclusive environmental policy improvements.